POTENSI DAN EFEKTIVITAS PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SEBAGAI PAJAK DAERAH DI KABUPATEN KAYONG UTARA - ME, JUNAIDI FIRRAWAN (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT In accordance with Law No. 28 Year 2009 on Regional Taxes and Levies, BPHTB is one type of tax that the authority of the district / city starting from January 1, 2011. BPHTB a local tax diversion is a strategic step in the implementation of fiscal decentralization, which can increase revenue. Thesis titled Harvesting Potential and Effectiveness of Tax on Acquisition of Land and Building the Local Taxes in the District of North Kayong, by Junaidi Firrawan, aims to analyze the potential BPHTB, analyze the effectiveness and efficiency of collection BPHTB, and analyze the constraints faced by the Government of the District of North Kayong in voting BPHTB. Judging from the potential BPHTB obtained from the study, in 2013 estimated there are 40 types of transactions and the acquisition of land and buildings with a value of Rp 6, 152,750,000. Whereas in 2014 there were an estimated 96 types of transactions and the acquisition of rights to the value of Rp 8, 014,925,000. The increase is supported by the potential increase in the base price of land and the adjustment of Tax Object Sale Value (SVTO). The effectiveness of tax collection BPHTB before becoming area from 2008-2010 is very effective, it is caused BPHTB has long been a central tax, availability of infrastructure, personnel resources in Ketapang STO has been inadequate, and supported by information technology-based application system . After a local tax collected by the Government of North Kayong, in 2011 amounted to 2.54% effectiveness rate or ineffective, this is due in 2011 was a transitional period BPHTB diversion, resource limitations, a new regulation set in the current year, the means and inadequate infrastructure, and system applications are not yet available. But in 2012, the rate increased by 177.55% effective or very effective. If viewed from the Tertiary efficiency, BPHTB collection in 2011 amounted to 56,92% or adequate efficient and 0.36% in 2012 or very efficient. Constraints faced in the collection in the District of North Kayong BPHTB is (1) The internal resistance (delay determination of regulatory, institutional, limited infrastructure, data and information technology systems are not yet available, and the quality and quantity of personnel is limited), and (2) Barriers external (late submission of data, coordination is still weak, limitations Notary / PPAT, lack of awareness and taxpayer compliance, transaction data manipulation, where services are limited, and the range is very wide and remote areas). Keywords: BPHTB, potency, effectiveness, efficiency